Analisis Ekspresi Interleukin-17 pada Karakteristik Klinikopatologi Karsinoma Payudara - Nyiayu Fauziah Kurniawati; Ika Kartika; Citra Dewi; Theodorus (Majalah Patologi Indonesia, 2021)
BackgroundInteraction between cancer cells and tumor microenvironment plays roles in cancer proliferation and invasiveness. Many type ofcytokine produced by inflammatory cells in tumor stroma could stimulate tumor proliferation and invasiveness, such as interleukin-17.The aim of this study is to determine the correlation between IL-17 expression and clinicopathological characteristics of breast cancer.MethodsSerial cases study was performed by enrolling 40 paraffin block of breast cancer patients. Clinicopathological characteirstics werenoted, including age, histopathological subtype and grade, TILs, lymphovascular invasion and molecular subtype. TILs were scoredby denomination area of stromal tissue occupied by mononuclear cells over total stromal area. Expression of IL-17 was examined byusing immunohistochemistry with anti-IL-17 antibody and counted from stromal mononuclear cells cytoplasm staining from five areas.The average value was used as a cut-off point in determining level of expression. Data were analysed by using SPSS v.22.ResultsMajority of the patients were more than 40 years old (75%), histopathological grade III (77.5%), without lymphovascular invasion(62.5%), luminal B molecular subtype (57.5%), and non-dominant TILs (95%). IL-17 expression was not significantly correlated withclinicopathological characteristics with p value=0.079, 0.600, 0.739, 0.883 and 1.000 respectively for age, histological grade,lymphovascular invasion, molecular subtype and TILs.ConclusionInterleukin-17 expression and clinicopathological on characteristics of breast carcinoma between histopathological grade, TILs, andlymphovascular invasion showed no significant differences. There was a tendency that the higher IL-17 expression, the higherhistopathological grade, the lower TILs and positive lymphovascular invasion